A Double-Injection Control Strategy For Partially Premixed Combustion. Issue 11 (2016) - Ingesson, Gabriel; Yin, Lianhao; Johansson, Rolf; Tunestål, Per
Abstract: Partially Premixed Combustion has shown to be a promising internal combustion concept in terms of engine efficiency and emission levels, however, since the combustion process is partly kinetically controlled, unacceptably high pressure-rise rates could occur at various operating points. A remedy to this problem is the use of a pilot-fuel injection. This paper characterizes double injection effects on combustion through experimental results and presents a double injection closed-loop model predictive control strategy where the combustion phasing is controlled arbitrarily as the pressure rise rate is controlled below a upper bound. Experimental results show promising response times during set-point changes as well as load and speed disturbances.